2008
DOI: 10.1590/s0102-76382008000200020
|View full text |Cite
|
Sign up to set email alerts
|

Mixoma gigante em átrio esquerdo: relato de caso

Abstract: A 63-year-old-woman with history of dispneia, palpitation and precordial discomfort was examined. The physical examination failed to reveal abnormalities. The diagnosis of cardiac tumor was accomplished with the help of bidimensional echocardiography, computadorized tomography and hemodinamic study. The operation was completed and the diagnosis of myxoma was confirmed by histopathologic study. The post-operative regarding the diagnosis was done in the present report, including the development of pleural effusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 6 publications
0
9
0
5
Order By: Relevance
“…They may arise in other locations, such as the right atrium (RA) (18% of cases) [5], and, more rarely, in the aorta, pulmonary artery, ventricles, vena cava, or even other organs [3,6]. The differential diagnosis is performed mainly between rhabdomyoma or thrombus [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…They may arise in other locations, such as the right atrium (RA) (18% of cases) [5], and, more rarely, in the aorta, pulmonary artery, ventricles, vena cava, or even other organs [3,6]. The differential diagnosis is performed mainly between rhabdomyoma or thrombus [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although this tumor presents with benign histological features, the signs and symptoms caused by myxomas are atypical and highly variable and can result in a difficult diagnosis of this neoplasia [3,8]. According to the size, mobility, and location of the tumor as well as physical activity and body position, patients' symptoms may have an asymptomatic course or progress with thromboembolic events that may even lead to sudden death [3,4,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Myxomas are the most common heart tumors, accounting for about 50% of benign primary cardiac tumors, with the majority located in the left atrium (LA), and 80% originate in the interatrial septum. Clinically, they often present themselves with signs and symptoms of mitral valve disease or thromboembolic events [1,2]. This is a patient with multiple left atrial myxoma, in case it is not mentioned in the literature, will be reported below.…”
Section: Introductionmentioning
confidence: 95%